بارودۆخی خیلافەتی عەبباسی لە سەدەی چوارەمی کۆچی/دەیەمی زایینی - ئەنوەر, دكتۆر كه یوان ئازاد; ئەحمەد, هیوا مەحموود (Sulaimani Journal for Humanities, 2021)
In order to shed light on the most important factors behindthe development of Islamic thought and civilization in the 4th century AH/ 10th century AD, we have extracted this chapter entitled "The circumstances of the Abbasid Caliphate during the 4th century AH/ 10th century AD". The current research has been re-formulated into three new divisions,; sheds light on the (political, economic, social, religious, and intellectual perspectives) during Abbasid caliphate. In addition to writing introduction, view most important resuits and refernces used in purly in research.